ANALISIS CORPORATE FINANCIAL PERFORMANCE, CORPORATE GOVERNANCE DAN CSR PERFORMANCE DI SEKTOR PARIWISATA DAN MULTIMEDIA - Rafaela Pertiwi Sergius; Etty Murwaningsari (Jurnal Magister Akuntansi Trisakti, 2016)
This research aims to identify the influence of Good Corporate Governance, represented by board size, independent commissioner size,institutional ownership, on CSR peformance and corporate financial performance, and also to observe the possible influence of CSR peformance on corporate financial performance . The population used in this study are multimedia and tourism companies listed on the Indonesia Stock Exchange(IDX) that chooses for the period of 2011 to 2014 as the sample. Sample selection procedure carried out by implementing purposive sampling method. Data are analyzed using path analysis.The results  suggest good corporate governance, represented by  independent commissioner size and blockholder ownership have positive influence toward CSR performance. Good corporate governance, represented by board size have no influence toward CSR performance . While, corporate governance represented by board size have positive influence toward corporate financial performance , independent commissioner size and blockholder ownership not have influences toward corporate financial performance and that only board size have direct and indirect effect toward corporate financial performance by CSR peformance.